Cyclophosphamide therapy in pediatric multiple sclerosis - Makhani, N (American Academy of Neurology, 2009)
OBJECTIVE: To review our multicenter experience with cyclophosphamide in the treatment of children with multiple sclerosis (MS). METHODS: Retrospective chart review of children with MS treated with cyclophosphamide. Demographic, clinical, treatment, and MRI parameters were collected. RESULTS: We identified 17 children with MS treated with cyclophosphamide. All but one had worsening of Expanded Disability Status Scale scores or multiple relapses prior to treatment initiation. Children were treated with one of three regimens: 1) induction therapy alone; 2) induction therapy with pulse maintenance therapy; or 3) pulse maintenance therapy alone. Treatment resulted in a reduction in relapse rate and stabilization of disability scores assessed 1 year after treatment initiation in the majority of patients. Longer follow-up was available for most cases. Cyclophosphamide was well tolerated in most patients. However, side effects included vomiting, transient alopecia, osteoporosis, and amenorrhea. One patient developed bladder carcinoma that was successfully treated. CONCLUSIONS: Cyclophosphamide is an option for the treatment of children with aggressive multiple sclerosis refractory to first-line therapies. Recommendations regarding patient selection, treatment administration, and monitoring are discussed. GLOSSARY: ARR: = annualized relapse rates; EDSS: = Expanded Disability Status Scale; IVIg: = IV immunoglobulin; MS: = multiple sclerosis; PLEX: = plasmapheresis; RRMS: = relapsing remitting multiple sclerosis; SPMS: = secondary progressive multiple sclerosis.